STUDI PEMANFAATAN AIR TANAH DALAM MEMENUHI KEBUTUHAN VILLA DI DESA KEROBOKAN KELOD KUTA - Sunar Jaya, I Gede; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2014)
ABSTRAK The government activity has development in every year. The development has side effect is about tourism development such as developing villa in Bali. One of villa has increase development at kerobokan kelod. Instrument used 30 sample of villa. This research is about development of villa and water utilization in that villa. Types of data and data sources used qualitative data that is taken from primary data and secondary data. Data collection by doing observation, in-depth interviews, documentation, literature study, and research instruments such as interview guides. The analysis of data using qualitative data analysis that is clearly presented findings based on the problems studied by accurate data source. Informant sampling used two methods are purposive sampling and survey. total sample informant using is 30 villa in kerobokan kelod village. Survey method used to know about the villa and to knowing how many water does the villa need. After that do the anal using quantitative description.
Keywords: Water utilization, ground water, and villa.